Factores psicosociales asociados al abandono paternal en padres entre los 18 y 24 años en el barrio Ondas del Caribe en Santa Marta D.T.C.H (2022)
The purpose of the project was to prepare a pre-feasibility study for a specialized maintenance services company for machinery components and heavy vehicles, hydraulic systems and power train. The theory is based on Cairo (2010), Baca (2013), Chain (2007), Chase, Aquilano and Jacobs, (2001), Córdoba (2014); Descriptive and documentary research, the approach is quantitative, the design is field, the general variable is the pre-feasibility study, the universe and population are made up of 13,050 pieces of equipment (machines and heavy vehicles) in the department of Atlántico. From the market it is concluded that the projection of the demand for the five years of the project is: 235, 254, 273, 291, 308 services to be offered respectively per year, market share at the end of the five years of the project of 36%, the offer o competition has a strong competitive power in the market, very few specialize in hydraulic components and power trains. The technical study showed that the capacity of the project is 235 services for the first year, the location will be Soledad (Atl), industrial warehouse, investment in machinery and equipment of $ 110.000.000, conditioning of the facilities of $ 55.000.000, transportation $34,000,000. The administrative study confirms that the type of company is S.A.S, the personnel cost for the base year is $179,992,309, investment in legal constitution $ 5,000,000, administrative expenses $ 59.110.000. The financial study established a profit of $ 84.852.000 for the first year of useful life, a minimum rate of return of 12%, a NPV of $ 709.018.851, and an IRR of 99, 57%.